Hyperhomocysteinemia, insulin resistance and body mass index in Iranian young women with polycystic ovary syndrome - Sedigheh Esmaeilzadeh; Eisa Tahmasbpour; Maryam Gholinezhad-Chari (Middle East Fertility Society Journal, 2017)
Objectives: Polycystic ovary syndrome (PCOS) is a common disease among young women that causes hyperinsulinemia. Hyperhomocysteinemia is shown to be correlated positively with the hyperinsulinemia. This study aimed to evaluate serum homocysteine (Hcy) level and its correlation with other serum metabolic amongst over weight, obese and non-obese PCOS women. Methods: Sixty women with PCOS and 20 healthy subjects were studied. Hormonal assays, lipid profile, Hcy and fasting insulin levels, insulin resistance (IR) indices (HOMA and QUICKI) determinations and ultrasound evaluation were performed. Results: Mean of BMI was significantly higher in PCOS subjects as compared with the controls (29.95 ± 4.91 vs 26.09 ± 4.80 kg/m2; p = 0.005). The mean fasting insulin levels were also significantly higher (17.80 ± 8.02 vs 11.55 ± 6.81 μU/dl; p = 0.003) where we found no difference in fasting glucose concentrations between groups. IR indices in PCOS women were significantly higher than control group (p < 0.01). We observed significantly higher mean serum Hcy levels in PCOS patients (11.68 ± 2.92 vs 9.31 ± 2.45 μmol/l; p = 0.047). When patients were stratified by BMI, the Hcy concentration was not significantly difference in both obese and normal-weight PCOS women. Fasting insulin concentrations and IR indices were significantly higher in obese PCOS patients as opposed to normal-weight PCOS women. IR indices showed increasing trends with BMI, but not Hcy levels. Conclusions: Our study shows the tendency toward hyperhomocysteinaemia, hyperinsulinemia and higher BMI in PCOS patients. These factors are critical predictors of PCOS; however, BMI and IR are an independent risk factor to increase plasma Hcy levels in PCOS women.